2018
DOI: 10.1016/j.gca.2018.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Stable and radiogenic strontium isotope fractionation during hydrothermal seawater-basalt interaction

Abstract: The fluid-rock interactions occurring in hydrothermal systems at or near mid-oceanic ridges (MOR) were studied experimentally by reacting crystalline and glassy basalt with seawater at 250 and 290 °C while monitoring the fluid phase Sr isotopic evolution (87 Sr/ 86 Sr and δ 88/86 Sr). The results indicate that seawater Sr was incorporated into anhydrite during the early stages of seawater-basalt interaction. Fluid 87 Sr/ 86 Sr values trend towards the basaltic signature as non-stoichiometric basalt dissolution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 91 publications
2
26
1
Order By: Relevance
“…Both have significantly higher δ 88/86 Sr yet similar 87 Sr/ 86 Sr to seawater, which is consistent with isotopic fractionation during precipitation, which enriches the solid phase in heavier isotopes. This is supported by an experimental study that found that anhydrite precipitation drove the composition of the liquid to isotopically lighter compositions, thus indicating that anhydrite has higher δ 88/86 Sr than liquid it precipitated from (Voigt et al, 2018). The extreme Sr isotope composition of the Messinian evaporites makes δ 88/86 Sr a potentially powerful tracer of the involvement of these evaporites in the source of the Aegean arc magmas.…”
Section: The δ 88/86 Sr Composition Of Subduction Zone Inputs 421 mentioning
confidence: 77%
See 3 more Smart Citations
“…Both have significantly higher δ 88/86 Sr yet similar 87 Sr/ 86 Sr to seawater, which is consistent with isotopic fractionation during precipitation, which enriches the solid phase in heavier isotopes. This is supported by an experimental study that found that anhydrite precipitation drove the composition of the liquid to isotopically lighter compositions, thus indicating that anhydrite has higher δ 88/86 Sr than liquid it precipitated from (Voigt et al, 2018). The extreme Sr isotope composition of the Messinian evaporites makes δ 88/86 Sr a potentially powerful tracer of the involvement of these evaporites in the source of the Aegean arc magmas.…”
Section: The δ 88/86 Sr Composition Of Subduction Zone Inputs 421 mentioning
confidence: 77%
“…The AOC composites show remarkably little variation in δ 88/86 Sr and only the most radiogenic 0-110 VCL composite sample has δ 88/86 Sr that is significantly heavier than unaltered MORB; all other AOC composites overlap with our data for N-MORB ( Figure 5b). The 0-110 m VCL composite sample plots towards the composition of 150-170 Ma seawater (McArthur et al, 2001;Vollstaedt et al, 2014) and has similar δ 88/86 Sr to the basaltic material altered by seawater in the experimental study of Voigt et al (2018). These authors found that alteration by seawater preferentially removes the lighter Sr isotopes from the basaltic host due to non-stoichiometric dissolution of crystalline basalt, but our results indicate that, at site 801, a positive shift in δ 88/86 Sr is only observed in the most strongly altered fractions of the upper oceanic crust.…”
Section: Mass-dependent Sr Isotope Systematics In (Altered) Oceanic Cmentioning
confidence: 79%
See 2 more Smart Citations
“…Geochemistry, Geophysics, Geosystems et al, 1988, Voigt et al, 2018. In contrast, the dissolution of anhydrite and admixing with seawater can directly influence the concentration of Sr and its isotopic composition.…”
Section: 1029/2019gc008694mentioning
confidence: 99%